Madrasa education in India eleventh to twenty first century (Kanishka Publ., 2005)
Contributed articles presented at the National Seminar on "Madrasa Education in India: Eleventh to Twenty 1st Century" in October 2002 at Jamia Millia Islamia, New Delhi.